2009
DOI: 10.1186/ar2821
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cytokine profiles in systemic sclerosis: associations with autoantibody subsets and clinical manifestations

Abstract: IntroductionSystemic sclerosis (SSc) (scleroderma) is a complex autoimmune disease that clinically manifests as progressive fibrosis of the skin and internal organs. Anti-centromere antibodies (ACAs), anti-topoisomerase antibodies (ATAs), and anti-RNA polymerase III antibodies (ARAs) are three mutually exclusive SSc-associated autoantibodies that correlate with distinct clinical subsets characterized by extent of cutaneous involvement and pattern of organ involvement. The current report sought to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
96
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 27 publications
11
96
1
4
Order By: Relevance
“…We found no statistically significant difference between serum IL-17 and IL-23 levels in dcSSc and lcSSc groups (p= 0.066 and p= 0.652, respectively), supporting the findings of Murata et al [12], as they could not find any difference between IL-17 levels of dcSSc and lcSSc [12]. In SSc pathogenesis, immune system dysregulation is thought to take part especially during the earlier stages [15]. In our study, no statistically significant difference was detected between disease duration and IL-17 and IL-23 levels in the non-parametric correlation analysis (p= 0.071and p= 0.257, respectively).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…We found no statistically significant difference between serum IL-17 and IL-23 levels in dcSSc and lcSSc groups (p= 0.066 and p= 0.652, respectively), supporting the findings of Murata et al [12], as they could not find any difference between IL-17 levels of dcSSc and lcSSc [12]. In SSc pathogenesis, immune system dysregulation is thought to take part especially during the earlier stages [15]. In our study, no statistically significant difference was detected between disease duration and IL-17 and IL-23 levels in the non-parametric correlation analysis (p= 0.071and p= 0.257, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…These results are similar to Murata et al, regarding IL17 levels [12]. On the other hand, Gourh et al, showed that as the disease progresses, IL-17 levels decrease, and IL-23 levels increase in the second decade after diagnosis [15]. Kurusawa et al also stated that IL-17 had an important role in SSc pathogenesis [11].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations